2022
DOI: 10.1101/2022.08.30.505699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Walk the Plank! Using mobile EEG to investigate emotional lateralization of immersive fear in virtual reality

Abstract: Most studies on emotion processing rely on the presentation of emotional images or films. However, this methodology lacks ecological validity, limiting the extent to which findings can generalize to emotion processing in the wild. More realistic paradigms using Virtual Reality (VR) may be better suited to investigate authentic emotional states and their neuronal correlates. This preregistered study examines the neuronal underpinnings of naturalistic fear, measured using mobile electroencephalography (EEG). Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…As hypothesized, we found stronger relative right-hemispheric activation in response to naturalistic compared to pictorial nauseating stimuli indicating that the method of presentation not only affects behavioral but also cerebral responses associated with avoidance and negative affect. These findings suggest that naturalistic stimuli are superior in emotion research and that pictures are suboptimal to induce affective states in line with other studies that failed to find changes in asymmetry using pictorial stimuli (31,(52)(53)(54). It could be argued that these results could be attributed to higher arousal resulting from the presentation of naturalistic stimuli.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As hypothesized, we found stronger relative right-hemispheric activation in response to naturalistic compared to pictorial nauseating stimuli indicating that the method of presentation not only affects behavioral but also cerebral responses associated with avoidance and negative affect. These findings suggest that naturalistic stimuli are superior in emotion research and that pictures are suboptimal to induce affective states in line with other studies that failed to find changes in asymmetry using pictorial stimuli (31,(52)(53)(54). It could be argued that these results could be attributed to higher arousal resulting from the presentation of naturalistic stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding negative emotions, fMRI studies have incorporated real human interactions such as insults by the experimenter to invoke feelings of anger in the participants ( 29 , 30 ). A mobile EEG study has investigated the neural correlates of fear comparing a virtual plank-walking task eliciting strong and immersive fear reactions compared to the presentation of IAPS pictures in a within-subject design ( 31 ). Here, only the plank task was related to stronger relative frontal alpha power associated with stronger right-hemispheric activation ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…A promising way to study the impact of emotional processing on motor control in settings resembling more real-life social situations is to employ virtual reality to build three-dimensional avatars. Such an approach will allow the creation of naturalistic events while maintaining a highly controlled experimental environment ( Basbasse et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pavic et al [45] highlighted encouraging results regarding the effectiveness of VR in fostering positive emotions. Additionally, Basbasse et al [46] suggested that stronger experiences of emotions, particularly fear, in VR tasks are associated with higher levels of asymmetry for negative emotions. This indicates that VR can elicit intense emotional responses, potentially leading to a decrease in negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is essential to note that the impact of VR on emotions is not universally positive. It has been found that negative emotions intensified by VR were correlated with negative rumination; for example, Basbasse et al [46] indicated potential negative emotional consequences of VR experiences. Furthermore, Li et al [48] highlighted that the negative effects of immersive VR were associated with a reduction in felt pleasantness, indicating potential negative emotional outcomes.…”
Section: Individual Panas Itemsmentioning
confidence: 99%